Enhanced interfacial adhesion of aramid fiber III reinforced epoxy composites via low temperature plasma treatment. (December 2018) - Fan, Wei; Tian, Huixia; Wang, Honghong; Zhang, Tao; Yang, Xue; Yu, Yang; Meng, Xue; Yu, Xichen; Yuan, Linjia; Xu, Bugao; Wang, Shujuan
Abstract: This paper investigated three process conditions in low temperature plasma treatment using orthogonal array experiments to optimize interfacial adhesion of aramid fiber (AF) III reinforced epoxy composite. The interfacial shear strength (IFSS) of the AF III in the epoxy was measured by single-fiber fragmentation test. Based on the range analysis results, the order of significant factors for IFSS is treatment power > treatment time > treatment pressure. The IFSS increased by 35.5% to 30.44 MPa under optimal conditions, which was found to be treatment power of 67.5 W, treatment time of 11 min, and treatment pressure of 2500 Pa. The interfacial reinforcing mechanism was explored by analyzing the surface morphology, chemical composition, wettability of the AF III, and the cross-section morphology of the broken single fiber-composite. Results indicated that Van der Waals' force, interfacial friction, interfacial wettability and chemical bonding were responsible for the interfacial improvement. Highlights: Enhanced interfacial adhesion of aramid fiber III and epoxy via plasma treatment. Investigated optimized plasma treatment conditions using orthogonal experiments. The interfacial shear strength was measured by single-fiber fragmentation test. Order of significant factors for interfacial performance is power > time > pressure. The interfacial reinforcing mechanism was explored by physico-chemical analysis.